EU FAST TRACK MEMBERSHIP: CAN IT HELP UKRAINE RESOLVE ITS REAL PROBLEMS? (Margalla Papers, 2023)
In 1991, during its inception process, Ukraine faced Russia's territorial claims and a cold reception from the Western world towards its leadership. After evaluating its internal and external interests, Ukraine chose to sign a friendship and cooperation agreement with Russia, compromising its rights as a sovereign state. This decision kept the complex issues of cross-border irredentism and multiple identities in check. However, during the democratic transition, external actors got involved in Ukraine's domestic politics, resulting in the removal of President Yanukovych's government. This critical juncture set the trajectory for unleashing Ukraine's state-ness issues. External involvement and political mismanagement aggravated Ukraine's problems and transformed its political issues into state-legitimacy issues, making its claim of a single entity void. Without state legitimacy, Ukraine cannot join the EU or consolidate as a democracy. Even if it enters the EU, it cannot safeguard its state sovereignty or achieve a profitable deal. This post-positivist research uses process tracing within a case study to highlight Ukraine's real problems and whether EU membership can help resolve them. The best solution for Ukraine is to focus on its domestic issues and negotiate with the other actor for a peaceful solution. Bibliography EntrySiddiqi, Houma. 2023. "EU Fast Track Membership: Can It Help Ukraine Resolve Its Real Problems?" Margalla Papers 27 (1): 13-27.